Prevalence and Correlates of Functional Limitation among Elderly in Kerala - Anjana, A; Chacko, Asha T (International Research Journal of Management, IT & Social Sciences, 2014)
Performance of IADL could be closely related to biological variables such as age and sex. Since women outnumbered men among the sample population, it is hopeful to conclude that elderly women can be relished with functional independence, but in the advancement of their age, they have to suffer a lot. The results of the study showed that the extended life year is accompanied by increased demands on health care delivery systems as more part of life may be spent with some functional limitation. The prevalence of physical disability in elderly persons with functional limitation are, therefore, important for policy development on care of the elderly. The most effective way to reduce the proportion of population with disabilities is to delay the onset of disabilities. Living independently in familiar surroundings surely promotes a better ageing and the development of living environments together with functional ability exert a profound influence on active ageing. In Kerala situation, geriatric care should be focused to the necessities of elderly women since they have to live more years with functional limitation and disability than males.Â